Behavior of plastic and metal ameroid constrictors during in vitro incubation in physiologic solutions of varying glucose concentration. (April 2016) - Griffin, Maureen A.; Hunt, Geraldine B.; Epstein, Steven E.
Abstract: The objective of this study was to evaluate the influence of ameroid constrictor (AC) composition as well as glucose concentration in the surrounding fluid on the rate and completeness of AC closure. In a pilot study, four ACs (two metal, two plastic) were incubated in a solution containing 100 mg/dL glucose, and in a follow-up study, two additional ACs (one metal, one plastic) were incubated in a solution of 100 mg/dL glucose and six ACs (three metal, three plastic) were incubated in a solution of 50 mg/dL glucose. Dimensions of the ACs were analyzed weekly for 57 days. No significant difference was found in the rate or overall proportionate closure for either metal versus plastic ACs or ACs incubated in 50 mg/dL versus 100 mg/dL glucose. As there was no statistically significant difference in the proportionate closure of metal and plastic ACs, both types are clinically suitable for gradual attenuation of portosystemic shunts in animal patients. The lack of a significant difference in rate and completeness of closure of ACs incubated in different concentrations of glucose provides evidence that the glucose concentration of the surrounding fluid likely does not have a significant effect on AC closure. However, a significant difference in the proportionate closure of ACs occurred within the first week of the study between constrictors incubated in 50 mg/dL glucose and those incubated in 100 mg/dL glucose, and additional studies are indicated to determine the significance of this early difference in vivo. Highlights: No significant difference in the proportionate change in internal diameter between metal and plastic ameroid constrictors. Ionized calcium leaches from the ameroid clay into the surrounding fluid (perfusate) in the first few days after immersion. Glucose concentration of the perfusate has no discernible effect on rate or completeness of ameroid constrictor closure.